Application of design of experiments (DoE) to dissolution method development in pharmaceutical industry - Souza, Renato Cesar de (2017)
The aim of this work is to apply design of experiment methodologyin the development of a dissolution method during the early phase ofdevelopment of a generic product in pharmaceutical industry. The model drug used during the development was the biphasic release product Zolpidem CR, which contains 12.5 mg of Zolpidem Hemitartrate per tablet. Previous to experimental design, a Failure Mode and Effect Analysis (FMEA)was performed to choose the most important variables.Four variables were considered the most importants to affect product release rate, which wereapparatus, rotation speed, volume and pH of the dissolution media. The variables selected were analysed by the full factorial design with the objective to identify the principal factors. The most critical factors were then used to construct the response surface model in order to model all variables and understand its interaction. The objective at this phase of product development was to reach anin vitro dissolution similar to the one in vivo, therefore all the responses were based on the in vivo absorption rate of the reference product obtained from literature. The mean Zolpidem plasma concentration-time profiles was deconvoluted by Wagner Nelson method and the deconvoluted curve was modeled to Logistic model. The parameters of the equation wereused as reference response. The responses monitored were the percentage dissolved in 0.25, 4.0 h, and the α ,β and R2 parameters of logistic equation. The model reliability and significance of the factors studied was evaluated by the analysis of variance (ANOVA). Two methods were used to determine the best dissolution condition, the first one was the Desirability Function and the second was the response surface sobreposition. The dissolution condition of basket with a rotation speed of 50 rpm and dissolution media of HCl 0,01 M (pH 2,0) with a volume of 500 ml was choosen as the condition that satisfied the desirability criterias stablished at the beginning of the experiment. The design of experiment methodology proved to be a more efficient methodology comparade to the traditional one factor at time (OFAT) method, reducing the number of experiments, number of samples and time to method development. The comprehension of the factors that affect release rate of the product and conclusion showed to be significantly superior to the traditional method.